Sent / 2. - Haddix, Margaret Peterson (Missing, 2009)
Jonah, Katherine, Chip, and Alex find themselves in 1483 at the Tower of London, and discover that Chip and Alex are Prince Edward V and Richard of Shrewsbury, imprisoned by Richard III; but trying to repair history without knowing what is supposed to happen proves challenging.